2013
DOI: 10.1371/journal.pone.0084100
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the Nonmatch-to-Goal rule in Monkeys across Cognitive Domains

Abstract: To solve novel problems, it is advantageous to abstract relevant information from past experience to transfer on related problems. To study whether macaque monkeys were able to transfer an abstract rule across cognitive domains, we trained two monkeys on a nonmatch-to-goal (NMTG) task. In the object version of the task (O-NMTG), the monkeys were required to choose between two object-like stimuli, which differed either only in shape or in shape and color. For each choice, they were required to switch from their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
(91 reference statements)
1
5
0
Order By: Relevance
“…Our results show that both monkeys started interacting at the beginning of the session and continued in a constant and continuous way for a substantial number of trials (500 for monkey L and 200 for monkey N). In terms of the number of trials performed, our results are comparable with those reported by a previous study conducted using a similar task but in an experimental setup where the monkeys worked in a primate chair 50 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results show that both monkeys started interacting at the beginning of the session and continued in a constant and continuous way for a substantial number of trials (500 for monkey L and 200 for monkey N). In terms of the number of trials performed, our results are comparable with those reported by a previous study conducted using a similar task but in an experimental setup where the monkeys worked in a primate chair 50 .…”
Section: Discussionsupporting
confidence: 88%
“…The NMTG task is considered to be a task with a high cognitive demand, because the monkeys are required to apply a counterintuitive rule 47,[50][51][52][53][54] and continuously monitor the trials performed, because the correct choice in one trial depends on the previous trial. We showed that this task could be learned using a home-cage training approach.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently examined the ability of monkeys to coordinate (Fujii et al 2007;Yoshida et al 2011) or cooperate (Mendres and de Waal 2000) with each other. It emerges from these studies that monkeys are able to monitor other agents' choices and their outcome and to use this knowledge to guide their own decisions (Chang et al 2011;Falcone, Brunamonti, Ferraina et al 2012;Bevacqua et al 2013;Falcone et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Future studies on abstraction should be planned to test whether the task variables encoded in an abstract form, as opposed to those that are not, would facilitate the generalization of the rules to new items or conditions. The ability of generalization has been reported by several studies on macaques [37, 38, 39, 35]. For example, Falcone et al [39] have shown that monkeys can transfer the nonmatch-to-goal rule from the object domain to the spatial domain in a single session, and Sampson et el.…”
Section: Discussionmentioning
confidence: 92%
“…The ability of generalization has been reported by several studies on macaques [46, 47, 48, 44]. For example, Falcone et al [48] have shown that monkeys can transfer the nonmatch-to-goal rule from the object domain to the spatial domain in a single session, and Sampson et el.…”
Section: Discussionmentioning
confidence: 92%